High emissions, low ambition: an institutional perspective of climate action in China and India - Afraa Aijaz (Nanyang Technological University, 2023)
The need to take climate action is increasingly becoming urgent and this has been echoed in COP26 and COP27. Yet, why are China and India, which are among the top largest GHG emitting countries, still taking insufficient climate action? As important as it is to understand, existing literature has not analysed this phenomenon. By applying discursive institutionalism as a conceptual framework and case study methodology to analyse and compare each country’s nationally determined contributions (NDCs) and long-term low emissions development strategy (LT-LEDS) documents, this paper has contributed to existing literature by uncovering the institutional factors causing China and India to take insufficient climate action. These factors include 1) capitalizing on developing country status, 2) limited and unambitious approach to climate action, 3) lack of responsibility for climate change and 4) prioritization of national interests. The findings have implications for China and India to adopt climate mitigation strategies with co-benefits as well as for UNFCCC to change its country-classification system to better hold both countries accountable for their climate action.